Meningkatkan Kemampuan Mengenal Fungsi Makan Sehat Dengan Menggunakan Metode Demonstrasi Pada Anak Usia Dini - Hasnawati Paputungan (Peneliti.net, 2022)
Based on observations made at GMIM Hosiana Tumatantang Tomohon Kindergarten in terms of creativity not yet optimal, this can be seen when learning activities with material on getting to know healthy food do not have the courage to explore and express themselves, children are doubtful, afraid, not confident, more often imitating the way of the teacher or other friends, the child still depends on the example given by the teacher, or the child still imitates the way the teacher completes his work. It can be observed that out of 15 children, 9 children were able to name, point to, and distinguish between healthy and unhealthy foods, while the other 6 children were not able to name and point to healthy and unhealthy foods. The purpose of this study was to describe the ability to recognize the function of healthy food using the demonstration method for children at GMIM Hosiana Tumatantang Tomohon Kindergarten. The research method used is classroom action research. In cycle I there were 9 out of 15 children who were declared successful because they had shown good development in terms of knowing healthy food. Thus the learning outcomes of children are only around 66.67% of the 80% target, so this classroom action research needs to be continued in the next cycle. In cycle II there were 14 children out of 15 who were declared successful, because they had shown good development in terms of recognizing healthy food. Thus, the learning outcomes of the children were around 93.33% of the target of 80% which were successful, so that class action research cycle II was declared successful. and no need to continue in the next cycle